2009
DOI: 10.1086/599031
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Human Influenza A (H5N1) Infection in Vietnam: 2004–2006

Abstract: In cases of infection with Influenza A (H5N1), the presence of both neutropenia and raised serum transaminase levels predicts a poor outcome. Oseltamivir treatment shows benefit, but treatment with corticosteroids is associated with an increased risk of death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
133
3
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(147 citation statements)
references
References 41 publications
9
133
3
2
Order By: Relevance
“…An acute respiratory disease characterizes H5N1 influenza virus infection in humans (1,5,13). The respiratory tract is the site of virus replication, and a combination of host-virus interactions modulates the severity and outcome of the disease.…”
Section: Resultsmentioning
confidence: 99%
“…An acute respiratory disease characterizes H5N1 influenza virus infection in humans (1,5,13). The respiratory tract is the site of virus replication, and a combination of host-virus interactions modulates the severity and outcome of the disease.…”
Section: Resultsmentioning
confidence: 99%
“…Some autopsy reports indicate that infection was limited to the respiratory and gastrointestinal tracts (9, 20), while others have isolated virus from the brain and gastrointestinal tract (21) or serum and cerebrospinal fluid (CSF) (22)(23)(24) or detected viral mRNA in the brain (21, 25). Measurements from blood samples taken early during the infectious period link severe disease outcomes with lymphopenia and hypercytokinemia (2,10,14,26), while the presence of high loads of negative-sense …”
mentioning
confidence: 99%
“…During an H5N1 outbreak, when the supply of oseltamivir may be limited, its prescription may be prioritized to individuals in high-risk exposure groups; for example, people who have had close contact with H5N1 virusinfected birds or patients (28). For a better-informed decision when prioritizing oseltamivir treatment, a more precise understanding of what constitutes high-risk groups is required, because for natural exposure, the source of virus is ambiguous, usually based on an anecdote provided by the patient or the patient's family (26). Furthermore, the characterization of high-risk exposure is based on the assumption that all mucosal sites of initial viral deposition are equally permissive to infection; however, differences between mucosal sites, such as receptor distribution, temperature, and pH, may contradict this assumption.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of H5N1 patients present with diarrhea. In fact, one retrospective report documenting the clinical features of H5N1 in Vietnam found that diarrhea was more common in fatal than nonfatal H5N1 cases [23].…”
Section: H5n1mentioning
confidence: 99%